Tumor lysis syndrome signal with the combination of encorafenib and binimetinib for malignant melanoma: a pharmacovigilance study using data from the FAERS database - Xia, Shuang; Xu, Jing-Wen; Yan, Kang-Xin; Noguchi, Yoshihiro; Sarangdhar, Mayur; Yan, Miao (Frontiers in Pharmacology, 2024)
Objective: To investigate the potential association between tumor lysis syndrome (TLS) and drugs for the treatment of malignant melanoma (MM).Methods: Reports of TLS recorded in the FDA Adverse Event Reporting System (FAERS) (January 2004-2023q3) were identified. Demographic and clinical characteristics were described, and disproportionality signals were assessed through the Reporting Odds Ratio (ROR) and Information Component (IC). The latency of TLS with anticancer drugs was described based on parametric models. Subgroup analysis was conducted to explore the differences of TLS signals in different age and sex.Results: We found 5(1.49%), 59(17.61%), 79(23.58%), 19(5.67%), 13(3.88%), 13(3.88%), 33(9.85%), 49(14.63%), 16(4.78%) TLS reports with pembrolizumab, nivolumab , ipilimumab, dabrafenib, vemurafenib, dacarbazine, "encorafenib and binimetinib" , "nivolumab and ipilimumab" , "dabrafenib and trametinib", respectively. The combination of encorafenib and binimetinib showed the strongest signal of TLS (IC 025 =3.98). The median days of latency of TLS with combination of encorafenib and binimetinib is 2days, which was much shorter than nivolumab (22.0days) and ipilimumab (21.5days). TLS cases associated with drugs for MM were predominantly recorded in females and aged 25-65 years. After excluding confounding factors such as pre-existing diseases and co-treated drugs, the disproportionate signal of TLS with "encorafenib and binimetinib" remained strong..Stronger disproportionate signal of TLS was detected in MM patients using the combination of encorafenib and binimetinib than other drugs. Further research is needed to investigate the underlying mechanisms and identify patient-related predisposing factors to support safe prescribing of the combination of encorafenib and binimetinib.